Quality Improvement of Instrument Transformer Using Taguchi Experiment Method in PT. XYZ - Ziyaurrohman Alladany; Mokh. Suef (Institut Teknologi Sepuluh Nopember, 2020)
Up to this year, PT. XYZ has been experienced of increasing sales of instrument transformer products, along with increasing consumer demand. Quality is the most important thing in the manufacturing product. But on the production floor of PT. XYZ faces quality problems. Based on the 2018 production report from January to December the number of defective products is more than 2 %. The high defective products indicate that there needs to be an improvement in the production process as a form of effort to improve quality on an ongoing basis. However, to achieve these objectives the company must know which control factors have an effect on improving the quality of the product. This research is intended to assist companies in solving problems of multiresponse cases that occur in the case of instrumentation transformer defect products, it will be analyzed using Taguchi Experiment combined with the PCR- TOPSIS method to improve product quality. Based on the results of this research, the results obtained that using the PCR-TOPSIS method optimum conditions can be achieved in the oven temperature control factor 110°C, oven time 240 minutes, mixing temperature 60°C, mixing time 130 minutes, clamping pressure 3 bars, and time clamping 20 minutes. By using the optimum treatment settings can be achieved quality improvement in each response with the characteristics of the quality is larger is better, where the increase in power frequency response increases by 11.11% and the response of partial discharge increases by 39.17%.